The Impact of Promotion and Basic Immunization Counseling Program on Mother’s Knowledge and Attitude - Prihanti, Gita Sekar; Hasna, Alifah; Rusda, Azilu Falabiba; Prabandhari, Fitri Dwi; Mayrina, Hassita Wenda; Azzahrah, Miratunisa; Iskandar, Muhamad Taufan (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Immunization is an effort to actively create/increase the body's immunity to protect children from various diseases. However, Indonesian society's understanding of immunization still varies especially parental knowledge and behavior, which will be the main factor in immunization completeness for children, thereby reducing immunization coverage and immunity gaps. This research aims to determine the effect of promotion and counseling on the knowledge and attitudes of mothers with children over 2 years in the urban areas of Kaliombo and Manisrenggo, the working area of the Southern City Health Center. The research method is Quasi-Experimental with a one-group pre-post test approach. The sampling technique used Total Sampling with a sample size of 64 people. Data was collected in the form of knowledge and attitude questionnaires. Data were analyzed using descriptive statistical tests, Wilcoxon and multiple linear analyses. The research results related to knowledge show a p-value of 0.000 (p<0.05). In contrast, attitudes show a p-value of 0.000 (p<0.05), which means there is a significant increase in knowledge and attitudes after basic immunization counseling and education. Based on the linear regression test results, it shows that if knowledge increases by one score, then attitude also increases by 0.668. This research concludes that promotion and counseling impact knowledge and attitude.